2022
DOI: 10.1016/j.canrad.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Is cancer a prognostic factor for severe COVID-19, especially for breast cancer patients?

Abstract: The coronavirus disease 2019 (covid-19) pandemic has caused a global upheaval in our health care system. Our hospital facilities have been subjected to a major influx of patients and the prevention of cross-contamination has been a key issue in the spread of the virus. New recommendations for good hygiene practice and new recommendations for disease management have emerged to limit the spread of the virus and reorganize the provision of care in key services. Many studies have attempted to identify factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A major worry during this time was to protect the continuity of care of chronic disease patients. One particular at-risk group was oncology patients, who face increased risk of severe complications of COVID due to a weakened immune system and because of their need for continued treatment to avoid disease progression and further complications [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A major worry during this time was to protect the continuity of care of chronic disease patients. One particular at-risk group was oncology patients, who face increased risk of severe complications of COVID due to a weakened immune system and because of their need for continued treatment to avoid disease progression and further complications [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here’s the explanation. According to research ( 25 ) cancer patients in theseseries, cancer cannot be considered to be an independent prognostic risk factor. Recent prospective studies have shown that severe forms of COVID-19 are not directly associated with cancer and cancer treatments, but can be attributed to the many comorbidities andpoor general status of this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that over 80% of COVID-19 cases have mild symptoms, but 10–20% of COVID-19 cases go into a severe stage [ 3 ]. Elderly people, as well as those with cardiovascular disease, diabetes, chronic respiratory disease, or cancer, are at greater risk of developing severe disease [ 1 , 4 , 5 , 6 ], while in cancer patients, recent prospective studies have shown that severe forms of COVID-19 are not directly related to cancer and cancer treatment but can be attributed to multiple comorbidities and poor overall health in this patient population [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%